REVITALISASI PERKULIAHAN PATROLI KEAMANAN SEKOLAH UNTUK MENINGKATKAN KARAKTER DISIPLIN DAN PEDULI SOSIAL PADA MAHASISWA PPKN SEBAGAI BEKAL CALON EKSTRAKURIKULER - ahmad Muhibbin; Sundari Sundari (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2017)
The research aims were: 1) to describe the revitalization of subject “Patroli Keamanan Sekolah (PKS)” at PPKn FKIP UMS in order to discipline character reinforcement and social concern; 2) to describe the task achievement (Capaian Pembelajaran) to revitalize subject PKS; 3) to describe PKS lesson plan; 4) to draft the development of PKS in order to reinforce discipline and social concern of PPKn students as a extracurricular tutor. This was a research and development done by sequences in two years. The research subjects were all appropriate source persons such as lecturers, students, alumni, and other stakeholders. The in-depth interview, focus group discussion, observation, literature review and indexing were conducted to collect data while interaction analysis was used to data interpretation. Research found: 1) PKS revitalization was conducted by task achievement (CP), Lesson Plan (RPS), integrated lesson trough learning, workshop, and training; 2) CP was arranged by sequence starting from first meeting to last meeting (14) with all competencies such as knowledge, attitude, and life skill; 3) Lesson plan included: CP attitude and values, basic knowledge, special skills, knowledge mastering, managerial skill, method and strategy, assignment, scoring, monitoring and feedback needed the active role from students in term of: students attendance, group presentation, class discussion, student activity monitoring, and face to face evaluation.